The Role of Pelvic Exenteration in the Management of Locally Advanced Prostate Cancer - Ala'a Farkouh; Nassib Abou Heidar; Ryan W. Dobbs; Ibrahim Abu-Gheida; Muhammad Bulbul; Mohammed Shahait (Société Internationale d’Urologie Journal)
Locally advanced prostate cancer poses a clinical challenge for physicians. Despite the established role of radiotherapy and androgen-deprivation therapy in these cases, some patients with locally advanced disease experience recurrent disease or persistent disease with debilitating local symptoms, such as intractable pain and urinary symptoms. In this narrative review, we sought to evaluate the role of exenterative surgery in the management of locally advanced prostate cancer. From our search, we found that total pelvic exenteration or cystoprostatectomy represents a viable therapeutic modality to manage prostate cancer directly invading the bladder, lower urinary tract symptoms, debilitating pain caused by locally advanced disease, and as salvage treatment after failure of primary treatment among other applications. Reports on minimally invasive pelvic exenteration for prostate cancer were also retrieved, as this represents a feasible and effective treatment option for experienced clinicians. Pelvic exenteration may be an effective tool for the treatment of locally advanced prostate cancer in the surgeon’s armamentarium; however, further studies are needed to establish its role in improving survival and overall patient outcomes.